1999
DOI: 10.1590/s0101-81751999000200003
|View full text |Cite
|
Sign up to set email alerts
|

Cestodes in South American freshwater teleost fishes: keys to genera and brief description of species

Abstract: Keys to genera of cestodes in South American freshwater teleost fishes are provided, with diagnoses of genera and short descriptions of species. Two new genera are proposed, Chambriella gen.n. for Goezeella agostinhoi Pavanelli & Santos, 1992 and G paranaensis Pavanelli & Rego, 1989, and Brooksiella gen.n. for Amphoteromorphus praeputialis Rego, Santos & Silva, 1974. Nomimoscolex magna Rego, Santos & Silva, 1974, previously species inquirenda, is transferred to the genus Proteocephalus Weinland, 1858. Goezeell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 39 publications
(41 reference statements)
1
51
0
3
Order By: Relevance
“…Bothriocephalus acheilognathi has been reported in 13 states of the USA (Hoffman 1999;Choudhury et al 2006), and from the Great Lakes area (Marcogliese 2008). There is only one published record of B. acheilognathi from South America (Rego et al 1999), most probably as a result of the import of carp from Europe to Brazil (Cornelio Procopio, Parana). Records of B. acheilognathi from India, Iraq, Israel, Korea, Malaysia, the Philippines, Sri Lanka and Turkey confirm its wide distribution in Asia (Paperna 1996;Hoffman 1999).…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
“…Bothriocephalus acheilognathi has been reported in 13 states of the USA (Hoffman 1999;Choudhury et al 2006), and from the Great Lakes area (Marcogliese 2008). There is only one published record of B. acheilognathi from South America (Rego et al 1999), most probably as a result of the import of carp from Europe to Brazil (Cornelio Procopio, Parana). Records of B. acheilognathi from India, Iraq, Israel, Korea, Malaysia, the Philippines, Sri Lanka and Turkey confirm its wide distribution in Asia (Paperna 1996;Hoffman 1999).…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
“…Due to its fast colonization to almost all continents and its pathogenicity, B. acheilognathi caused worldwide concern as an important pathogenic and most dangerous fi sh tapeworm, which causes bothriocephalosis of feral but especially of cultured fi sh (Scholz et al, 2012). There are no records of B. acheilognathi published up to date from native fi shes of South America but only two fi ndings from introduced common carps: from Brazil, most probably as a result of the import of carp from Europe (Rego et al, 1999) and from Argentina, found in introduced wild population of Cyprinus carpio (Waicheim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Body surfaces were also examined for encysted metacercariae. For identification and diagnosis of parasites, the following references were used: Travassos et al (1969), Kohn et al (1995) and Gibson et al (1996) for trematodes, Moravec et al (1990) and Thatcher (2006) for nematodes, and Rego et al (1999) for cestodes. For species identification, parasites were analysed using a computerized system for image analysis (Qwin Lite 3.1, Leica Microsystems, Wetzlar, Germany).…”
Section: Introductionmentioning
confidence: 99%